2022
DOI: 10.1186/s12883-022-02908-7
|View full text |Cite
|
Sign up to set email alerts
|

Retinal microvasculature and cerebral hemodynamics in patients with internal carotid artery stenosis

Abstract: Purpose To investigate the relationship between retinal microvasculature and cerebral hemodynamics in patients with internal carotid artery (ICA) stenosis. Methods Patients with unilateral moderate or severe ICA stenosis(≥50%) from West China hospital, Sichuan university were consecutively and prospectively recruited enrolled in the current study. En face angiograms of the superficial vascular complex (SVC), deep vascular complex (DVC), superficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…However, Li et al (2019) did not observe of altered retinal or choroidal thickness in patients with ICAS. This suggests that there is not a parallel relationship between the degree of ICAS and retinal and choroidal thickness, but it may also be related to the presence of collateral anastomoses between branches of the ophthalmic artery and branches of the external carotid artery ( Liu J. et al, 2022 ). Poor collateral circulation between the internal and external carotid arteries, between the two internal carotid arteries, or even retrograde flow of blood from the ophthalmic artery may result in inadequate blood supply to the eye and changes in the morphological structure of the retina ( Lauria et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Li et al (2019) did not observe of altered retinal or choroidal thickness in patients with ICAS. This suggests that there is not a parallel relationship between the degree of ICAS and retinal and choroidal thickness, but it may also be related to the presence of collateral anastomoses between branches of the ophthalmic artery and branches of the external carotid artery ( Liu J. et al, 2022 ). Poor collateral circulation between the internal and external carotid arteries, between the two internal carotid arteries, or even retrograde flow of blood from the ophthalmic artery may result in inadequate blood supply to the eye and changes in the morphological structure of the retina ( Lauria et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…By early detection of microvascular changes in the retina in this patient group, we might speculate the overall vascular condition of patients and take timely measures to prevent further damage even before visual acuity is affected. Liu J. et al showed that retinal microperfusion changes in the superficial vascular layer were correlated with hemodynamic alterations in the brains of patients with moderate or severe ICA stenosis, demonstrating that retinal perfusion might give insight into cerebral perfusion [ 12 ]. Stenosis of the internal carotid artery would result in decreased blood flow to the choriocapillaris and central retinal artery, causing apoptosis of retinal ganglion cells, cone cells, and rod cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although no data on the BCAS-induced retinal tissue oxygenation are available, several studies have reported reduced retinal vascular density in subjects with carotid stenosis 75 78 Indeed, a recent study established a relationship between retinal vascular perfusion and cerebral hemodynamics in subjects with internal carotid artery stenosis 79 …”
Section: Discussionmentioning
confidence: 99%
“… 75 78 Indeed, a recent study established a relationship between retinal vascular perfusion and cerebral hemodynamics in subjects with internal carotid artery stenosis. 79 …”
Section: Discussionmentioning
confidence: 99%